Mimetic Analysis of “Black Sun” in the Korean Drama “Taxi Driver 2” With the Burning Sun Case - Khairunnisa, Siti; Ginting, Reza Pahlevi (SAINTIS Publishing, 2024)
This study explores the relationship between the real-life Burning Sun scandal and its fictionalized portrayal in the Korean drama “Taxi Driver 2”, specifically focusing on the episode titled